GENDER DIFFERENCES IN WORKING MEMORY PERFORMANCE - Zhi Shan, Chan (Universiti Malaysia Sarawak (UNIMAS), 2021)
This research is conducted to investigate the gender differences in working memory performance, in terms of both verbal and visuospatial working memory performance based on total number of correct recalled as well as total time taken. Thirty-two undergraduates from University Malaysia Sarawak (UNIMAS) were participated in this study. This study employed quantitative research method through quasi experimental design. Independent sample t-test was then adopted to test the hypotheses of the study. The findings showed that significance gender difference was observed in both verbal and visuospatial working memory performance based on total time taken, which males performed more rapidly than females in these tasks. In terms of accuracy which measured through calculation of total number of correct recalled, females were recalled better than males in verbal task as consistent to numerous previous studies. However, no gender difference was identified in visuospatial task based on total number of correct recalled, with males did not show advantage at visuospatial abilities as revealed by past studies. This study also discussed implications of the findings for a reference to future researchers.